Digital stress and friendship conflict in adolescence: the role of perceived norms and features of social media - Angelini, Federica; Gini, Gianluca (Frontiers in Digital Health, 2025)
IntroductionDigital stress, resulting from expectations of online availability, can increase the risk of conflicts with friends. However, friendship conflict remains an underexplored indicator, particularly in association with stressful online experiences. This study aims to examine the association between digital stress and conflict levels overtime, considering the role of social media expectations.Method1185 adolescents (59.3% f, Mage = 15.97 years, SD = 1.43) completed self-report measures at two timepoints, six months apart. A Structural Equation Model was employed to examine the longitudinal associations of social media expectations (i.e., friends' social media norms, friends' social media use, and perceived social media features) on friendship conflict, focusing on the mediating role of digital stress (i.e., entrapment and disappointment). Gender differences were explored.ResultsPerceived norms about social media use and unique features of social media (i.e., visualness) contributed to explain digital stress and, in turn, friendship conflict. Specifically, emotional responses to unmet expectations of availability on social media (i.e., disappointment) emerged as particularly relevant in explaining conflictual interactions, compared to the perceived pressure to be responsive to friends (i.e., entrapment). Males perceiving high availability of social media experience lower levels of entrapment, compared to females.DiscussionResults from this study support the importance of considering social media as a context where to study friendship dynamics, as this knowledge can have several implications for promoting positive online experiences and preventing conflicts with friends.